Comparative evaluation of Baccharis trimera, Pimpinella anisum and statin on the biochemical profile of Wistar rats - Sandra Maria Barbalho; Adriano Cressoni Araújo; Elen Landgraf Guiguer; Maricelma da Silva Soares Souza; Patrícia Cincotto dos Santos Bueno; Claudemir Gregório Mendes (International Journal of Phytomedicine, 2015)
Many are the plants for therapeutic purposes. Baccharis trimera is known to treat rheumatism, diabetes, and liver disorders. Pimpinella asinum is known to control colds, cough, bronchitis, fever, cramps and inflammation. The aim of this study was to evaluate the use of B. trimera and P. anisum and compare with statin effects on plasma lipids of Wistar rats. Sixty Animals were divided in control group (CG) and G2 (treated with anise), G3 (B. trimera) and G4 (simvastatin). Plants and statin were administrated by intra-gastric route twice a day for 30 days. No modifications in glycaemia were observed in the experimental groups. Reductions were observed in cholesterol levels in treated groups. For LDL-c levels, significant differences were observed in G2 and G4. G3 showed significant reduction in the triglycerides levels and no significant differences were observed in the glycaemia in the studied groups. Increased levels of HDL-c were presented by the groups treated with the plants. The group treated with B. trimera showed significant reduction in triglycerides when compared to the control group. The use of the plants also shows Atherogenic Index lower than control group and the one treated with simvastatin. Our results suggest that the plants used in this work have similar or better effects in the lipid profile of Wistar rats when compared to the use of statin.